Assessment of Consumers’ Religiosity Consciousness of Malaysian Green Personal Care Products - Bt Mohammad, Noorita; B. Baharun, Rohaizat (International Journal of Engineering and Technology, 2018)
Local green products are still very new for Malaysian businesses; therefore, there are only few studies that focus on consumerâ€™ purchase intention of green products. Green products are made from extracts of herbs as the main ingredient, and as such Muslim consumers have a high tendency to buy them because of their green content. Although studies have recognized religiosity consciousness as an important factor that affects the Muslimsâ€™ behaviour, there is less information about its effect on the consumersâ€™ decision in buying green products. The objective of this study is to investigate the relative importance of religiosity consciousness on purchase intention of green products as religiosity consciousness has not yet been extensively investigated in explaining the consumersâ€™ intention and behaviour towards buying green products. A self-administered survey was conducted in the form of a mall intercept with 250 female consumers. This study contributes to the improvement of our understanding of consumersâ€™ green decision making and the relevant marketing strategy for the local companies in the market. Surprisingly, the results shows insignificant relationships. The finding provides evidence that consumersâ€™ buying decision of green products is not influenced by religiosity consciousness. This article also includes discussion of theoretical and management implications.Â